2002
DOI: 10.1002/ppul.10163
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow stem cells do not repopulate the healthy upper respiratory tract

Abstract: Recent studies reported differentiation of both bone marrow and tissue-specific stem cells into cells of other organs. The demonstration that bone marrow stem cells differentiate into human hepatocytes in vivo has raised the possibility of new therapeutic approaches for liver disease. For diseases such as cystic fibrosis (CF), correction of the respiratory epithelium is being attempted by gene therapy. Differentiation of bone marrow stem cells into epithelium of the lung and airway was recently reported in an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 19 publications
1
17
1
Order By: Relevance
“…Other studies, however, have suggested that in some cases, bone marrow-derived cells may actually contribute to fibrosis (Epperly et al, 2003;Hashimoto et al, 2004;Phillips et al, 2004). Indeed, controversy remains about the actual ameliorative effect of circulating stem cells, whether or not they can engraft in other organs, and whether engrafted cells undergo fusion or transdifferentiation (Aliotta et al, 2005;Vassilopoulos et al, 2003;Wang et al, 2003;Chang et al, 2005;Davies et al, 2002;Kotton et al, 2005;Zander et al, 2005;Loi et al, 2006). Clearly, researchers have not yet reached a consensus about the role that circulating stem cells play in lung processes.…”
Section: Circulating Stem Cells and Applications In Lung Regenerativementioning
confidence: 96%
“…Other studies, however, have suggested that in some cases, bone marrow-derived cells may actually contribute to fibrosis (Epperly et al, 2003;Hashimoto et al, 2004;Phillips et al, 2004). Indeed, controversy remains about the actual ameliorative effect of circulating stem cells, whether or not they can engraft in other organs, and whether engrafted cells undergo fusion or transdifferentiation (Aliotta et al, 2005;Vassilopoulos et al, 2003;Wang et al, 2003;Chang et al, 2005;Davies et al, 2002;Kotton et al, 2005;Zander et al, 2005;Loi et al, 2006). Clearly, researchers have not yet reached a consensus about the role that circulating stem cells play in lung processes.…”
Section: Circulating Stem Cells and Applications In Lung Regenerativementioning
confidence: 96%
“…It is thus difficult to distinguish the implanted donor cells from the invading host cells. Human-specific antigens such as HLA or Y chromosome sequences [9] and human Alu sequences [4] have been used as human cell markers for hMSCs but detection requires refined techniques of immunocytochemistry or in situ hybridisation, for example. This makes it problematic to characterise the effects of the engineered products.…”
Section: Introductionmentioning
confidence: 99%
“…Wagers et al showed that transdifferentiation of circulating HSCs and/or their progeny is an extremely rare event, if it happens at all [25]. And it was reported that BMDCs would not repopulate the healthy upper respiratory tract [26]. Therefore, we doubted whether BMDCs could differentiate into intestinal epithelial cells in the long term in transplantation recipients and whether such a phenomenon would happen in recipients even without any special damage treatment.…”
Section: Discussionmentioning
confidence: 95%